STRATEGI KOMUNIKASI BISNIS DALAM MEMPERTAHANKAN MINAT BELI KONSUMEN KEBAB UNCLE HASAN - Firjatullah, Hafiz; Moenawar, Mohammad Ghozali; Suparman, Suparman; Muhammad, Badar; Manisya, Nabhila; Awalina, Salwa Putri (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
Business communication strategies play a significant role in influencing consumer purchase intentions, encompassing product quality, convenience, pricing, service, and promotions. Kebab Uncle Hasan, a rapidly growing kebab restaurant in Bogor, implements personal selling as its communication strategy. This study aims to analyze the implemented communication strategy and identify challenges in enhancing consumer purchase interest. This qualitative research explores the influence of descriptive analysis from the perspectives of both consumers and the management of Kebab Uncle Hasan. The findings reveal that the stages of personal selling highlighting product quality, responsive service, social media promotions, and innovations in seasoning packaging and authentic flavors are key factors in attracting and retaining customers. However, challenges remain in product variety and follow up strategies for customer engagement.